From Wibbleton to Wobbleton : adventures with the elements of music and movement - Harding, James, ....-; Noyes, Eli, ....- (San Francisco : Pentatonic Press, 2013)
In this collection, James Harding, long-time colleague and collaborator of Doug Goodkin and Sofia Lopez-Ibor at the San Francisco School, puts forth his uniquely playful take on Orff-Schulwerk. Starting with a rhyme, a riddle, a song or a simple prop, the book maps out delightful journeys of discovery designed to awaken the curiosity and creativity of elementary-aged students. Classroom teachers and experienced music specialists will find ideas and inspiration and ideas in this book, which models hands-on, ears-open exploration of the child's world, from eggs and chickens to the solar system. This unique book contains: over 30 different activities. Delightful, helpful illustrations by Eli Noyes (sometimes a picture is worth one thousand words!). Lessons integrating music and movement with language arts, math, and science. Lesson plans for music and classroom teachers. Arrangements for Orff instrument ensemble. Ideas for using the Orff-Schulwerk approach without Orff instruments. Reflections on the place of creative play in education. Ideas for teachers for developing their own materials.
Keywords: Bewegingsopvoeding -- Basisonderwijs; Muzikale vorming -- Basisonderwijs; Muzische vorming -- Basisonderwijs